Pengaruh parameter proses friction stir welding dengan material aluminium alloy AA6061-T651 terhadap distorsi dan kekerasan - Mulyadi Mulyadi; Rachmat Firdaus; Iswanto Iswanto; Mochammad Nur Rizki (TURBO [Tulisan Riset Berbasis Online], 2022)
Welding is a process of uniting two or more materials into a form of connection using heat energy. Friction Stir Welding (FSW) is a solid-state welding method that can produce high-quality welding joints for some materials with low weldability such as aluminum. The research objective was to determine the effect of process parameters on the distortion and resistance of aluminum AA6061-T651 material through the Brinell hardness test. The FSW tool used has a hexagonal pin geometry. The experimental design used the Taguchi method. This study uses 4 factors and each factor has 4 levels, the elements used are tool rotation speed, welding speed, tool tilt angle, and concave shoulder angle. The responses analyzed are distortion and hardness of the welded joint material. The effect of process parameters on the response was analyzed using ANOVA. The results of ANOVA on distortion obtained the value of Brinell hardness in the weld metal area, and in the TMAZ area. Specimen 13 with tool rotation speed parameters of 3022 rpm, welding speed of 43 mm/min, tool tilt angle of 3.5°, and concave shoulder angle of 2° with a distortion value of 0.117°. Then we get the results of the Brinell hardness of the weld metal which is close to the target of the base metal with the parameter tool rotation speed of 3022 rpm, welding speed of 90 mm/min, tool tilt angle of 2.5°, and concave shoulder angle of 8° with a Brinell hardness value of 75. 7 BHN, and the Brinell hardness value at TMAZ with tool rotation speed parameters of 1208 rpm, welding speed of 65 mm/min, tool tilt angle of 2.5°, and concave shoulder angle of 2° with a Brinell hardness value of 74.7 BHN.